CHANGES IN INTESTINAL MICROBIOCENOSIS IN PATIENTS WITH COVID-19 - Isakulova Muhabbat Mardanovna; Ibragimova Nadiya Sabirovna; Ibragimov Baхodir Fikriyevich; Uralova Dildora Alisherovna (TADQIQOTLAR.UZ, 2024)
Annotation.  Coronavirus  infection  remains  a  pressing  problem  of  modern healthcare. Despite the end of the pandemic stage, its spread, the likelihood of mutation and the emergence of new genetic lines of SARS-CoV-2, capable of causing significant epidemic increases in morbidity, predetermine the continuation of scientific research in the field of pathogenesis, a personalized approach to the treatment and rehabilitation of patients.